Risk factors for cesarean delivery in primigravida during spontaneous labor - Ma, Saung Oo; Cheng, Hui Ching; Hussin, Mohd Sharifullah Yahya; Ching, Siew Mooi (Pakistan Medical Association, 2015)
Objective: To identify the risk factors for cesarean delivery among primigravida at Hospital Serdang. Methodology: This was a case control study which involved total 260 of 130 primigravida patients that underwent cesarean section (cases) and 130 primigravida patients that underwent vaginal delivery (control) at obstetrics and gynaecology department of Hospital Serdang, Malaysia from January until June 2013. A standardized proforma was used to collect the data of each primigravida patient presenting in spontaneous labour at term with singleton pregnancy with either caesarean or vaginal delivery. Results: Majority of the cases were Malaysian (86.9%) and mostly were from Malay ethnic group (75.4%). In multivariate logistic regression analysis, presence of hypertension status (odds ratio [OR] 5.7, 95% CI; 1.56-20.84) and gestational age less than 40 weeks (OR 2.60, 95% CI 1.34-5.02), fetal weight more than 3000gm (OR 1.8, 95% CI 1.1-2.95), were associated with higher odds of cesarean delivery. Conclusion: Primigravida with presence of hypertension, having gestational age less than 40 weeks and heavier fetus were associated with higher odds of cesarean delivery.